Enhanced comprehensive two-dimensional gas chromatographic resolution of polychlorinated biphenyls on a non-polar polysiloxane and an ionic liquid column series - Zapadlo, Michal; Krupčík, Ján; Kovalczuk, Tomáš; Májek, Pavel; Špánik, Ivan; Armstrong, Daniel W; Sandra, Pat (Journal of chromatography. A, Including electrophoresis and other separation methods, 2011)
A total of 196 out of 209 polychlorobiphenyl (PCB) congeners were resolved using GC×GC-TOFMS with a non-polar/ionic liquid column series consisting of poly(50%-n-octyl-50%-methyl)siloxane and (1,12-di(tripropylphosphonium)dodecane bis(trifluoromethansulfonyl)amide) in the first and second dimension, respectively. It has been found that 13 PCB congeners overlap in five doublets (CB12+CB13, CB62+CB75, CB70+CB76, CB97+CB125 and CB153+CB168) and one triplet (CB90+CB101+CB113). All toxic, "dioxin like" congeners were separated with no interferences from any PCB congener. The 109 PCBs present in Aroclor 1242 and the 82 PCBs present in Aroclor 1260 were resolved GC×GC-TOFMS analysis on this column set.
Keywords: plynová chromatografie s hmotnostně spektrometrickou detekcí; Polychlorinated Biphenyls; iontové kapaliny; siloxany; polychlorované bifenyly; Gas Chromatography-Mass Spectrometry; Siloxanes; Ionic Liquids